Survey on SSDF attack and defense for distributed cooperative cognitive radio - Guangyue LU; Hang SU (Dianxin kexue)
Cooperative spectrum sensing (CSS) improves the reliability of spectrum sensing,however,it is susceptible to spectrum sensing data falsification (SSDF) due to the fusion mechanism.To insight into the current research and development trend of defense strategy against the SSDF attack,several typical distributed strategies were concluded and the types of distributed algorithms were analyzed in several aspects.Finally,the future research of SSDF distributed defense strategy was prospected based on the problems found in the current research.